PERBANDINGAN DUKUNGAN KELUARGA DAN PENERIMAAN DIRI PASIEN PRIA DAN WANITA DENGAN DIABETES MELLITUS TIPE II - Sebastianus Banggut; Febtian Cendradevi Nugroho; Tita Q. Dumalag (Nursing Arts, 2021)
The number of people with Diabetes Mellitus in all countries is predicted to increase. More than 400 million people are diagnosed with Diabetes Mellitus, especially in countries under the Asia Pacific region. Indonesia placed on the rank 7th in the top 10 countries with the highest population of Diabetes Mellitus and the Province of East Nusa Tenggara takes part with more than 3% of the population suffering from Diabetes Mellitus. Diabetes patient generally experience an emotional phase related to their condition and family support is important for their self-acceptance. Female Diabetes patien are more likely to show signs of depression and anxiety than male. In addition, the functions and roles of men and women differ in the family. This study aims to determine the comparison of family support with self-acceptance of male and female patients with type II diabetes mellitus. This is quantitative research with a cross-sectional design with the Spearman and Mann Whitney test. Respondents of this study were 20 male and 20 female who stay with their family. Purposive sample selection technique used in this study. The results of this study were 65% of male patients and 50% of female patients were classified as receiving adequate family support. As many as 70% of male patients and 90% of female patients are classified as having good self-acceptance. Based on the results of the Spearman test, data shows that there is no relationship between family support and self-acceptance of male and female patients with Type II Diabetes Mellitus. Thus, the conclusion of this study is that there is no significant difference between family support and self-acceptance of male and female patients with type II diabetes mellitus. For the recommendation, Health institutions could collaborate with related parties to maximize the role of the family as the main caregiver.